Effective utilization of waste cooking oil in a diesel engine equipped with CRDi system using C8 oxygenates as additives for cleaner emission. (1st September 2020) - Sharbuddin Ali, S.; Swaminathan, M.R.
Graphical abstract: Highlights: A blend of recycled fuel and renewable fuel was utilized in diesel engine. Comparative assessment of C8 isomers as oxygenated additives on engine characteristics were analyzed. Best among di-n butyl alcohol, 2-ethyl hexanol and 1-octanol were determined. Abstract: Utilizing waste cooking oil as fuel in diesel engines is advantageous as it addresses two major issues (a) reduces the risk of environmental problems (b) reduces fossil fuel dependency. In the present study, biodiesel produced from the waste cooking oil is tested along with the diesel and three oxygenates viz., di-n butyl ether (DBE), 2-ethyl hexanol (TEH) and 1-octanol (OCT) in a diesel engine equipped with CRDi system. For this purpose three ternary blends were prepared (a) D80-WCOME15-DBE5 (b) D80-WCOME15-TEH5 (c) D80-WCOME15-OCT5 and the effects of these oxygenates on the combustion, performance and emission characteristics was investigated at stock settings and compared with diesel and D80-WCOME20 blend. Results revealed that substituting 5% vol. of WCOME with oxygenates was beneficial in improving the combustion characteristics of the engine. Among the oxygenates 1-octanol blend showed higher HRR peaks. The BTE slightly dropped for ternary blends in comparison with the WCOME20 blend and was still higher than diesel. The NOx emission for ternary blends was comparatively higher than reference fuels, NOx emission increased by 0.02%, 1.75% and 4.07% for DBE, THE, and OCT blends respectively when compared to diesel. 1-Octanol blend showed 25.77% and 22.03% lower smoke opacity than DBE and TEH blends respectively. HC and CO emissions for ternary blends were low when compared to the reference fuels. Whereas CO2 increased with all the ternary blend. In summary, 1-octanol delivered the best performance and low emissions among oxygenates and could be an excellent additive when the engine is fueled with diesel/WCOME blends.